A low-temperature sintered thin ceramic tile and production method

Through the method of low-temperature sintering technology and the cooperation of raw materials, a dense cross-network structure is formed, which improves the damage strength and breaking modulus of thin ceramic tiles, solves the problem of poor damage strength of thin ceramic tiles, and achieves efficient and environmentally friendly ceramic tiles production.

CN119775037APending Publication Date: 2025-04-08HEBEI BOER CERAMICS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411743527.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The damage strength of thin ceramic tiles on the market is poor, which is difficult to meet the market's demand for ceramic tiles with small thickness and high damage strength.

Method used

Low-temperature sintering technology is adopted to form a dense cross-net structure by combining raw materials such as lene, potassium feldspar, sodium feldspar, mullite, quartz sand, micron metal oxides, scale graphite, aluminum borate whiskers, aluminum oxide fibers and other raw materials to form a dense cross-network structure, and improve the damage strength and fracture modulus of ceramic tiles.

Benefits of technology

The sintering of thin ceramic tiles under low temperature conditions is achieved to reduce energy consumption and exhaust gas emissions. The damage strength of ceramic tiles exceeds 960N, the fracture modulus exceeds 63MPa, and the water absorption rate is less than 0.2%, showing the advantages of high damage strength, fracture modulus and low water absorption rate, meeting market demand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163038400000041
    Figure BDA0005163038400000041
  • Figure BDA0005163038400000051
    Figure BDA0005163038400000051
Patent Text Reader

Abstract

The present application relates to the technical field of thin ceramic tile production, and specifically discloses a low-temperature sintered thin ceramic tile and a production method. The thin ceramic tile is mainly made of the following raw materials in parts by weight: 15-25 parts of pyrophyllite, 10-20 parts of potassium feldspar, 10-20 parts of sodium feldspar, 10-20 parts of mullite, 20-30 parts of quartz sand, 6-10 parts of micron metal oxide, 4-6 parts of flake graphite, 4-6 parts of aluminum borate whiskers, 6-8 parts of aluminum oxide fiber, 2-4 parts of metal aluminum powder, 1-3 parts of flux, 3-7 parts of ball clay, 8-12 parts of bentonite, and 13-17 parts of silica sol adhesive. The thin ceramic tile, through the mutual cooperation between the raw materials, can not only achieve low-temperature sintering, but also has the advantages of high breaking strength, high modulus of rupture, and low water absorption, improves the quality of thin ceramic tiles, expands the scope of application, increases the stability of use, prolongs the service life, and meets market demand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thin ceramic tile production, and more specifically, to a low-temperature sintered thin ceramic tile and a production method thereof. Background Art

[0002] Ceramic tiles have a long history in my country. They have been widely used because of their advantages of high hardness, strong fire resistance, good chemical resistance and easy cleaning. In particular, with the emergence of thin ceramic tiles, they have been increasingly used in the decoration of cabinets, wardrobes, counters, ceilings, curtain walls, etc. The thickness of traditional ceramic tiles is generally greater than or equal to 10mm, while the thickness of thin ceramic tiles is generally less than or equal to 7mm. Due to the small thickness of thin ceramic tiles, they can greatly save raw materials and energy, and reduce pollution emissions. However, the thin ceramic tiles on the market still have the problem of poor destructive strength. Therefore, the development of a thin ceramic tile with small thickness and high destructive strength is of great significance to meet market demand. Summary of the invention

[0003] In order to improve the destructive strength of thin ceramic tiles, the present application provides a low-temperature sintered thin ceramic tile and a production method.

[0004] In the first aspect, the present application provides a low-temperature sintered thin ceramic tile, which adopts the following technical solution: A low-temperature sintered thin ceramic tile, which is mainly made of the following raw materials in parts by weight: 15-25 parts of pyrophyllite, 10-20 parts of potassium feldspar, 10-20 parts of sodium feldspar, 10-20 parts of mullite, 20-30 parts of quartz sand, 6-10 parts of micron metal oxide, 4-6 parts of flake graphite, 4-6 parts of aluminum borate whiskers, 6-8 parts of aluminum oxide fiber, 2-4 parts of metal aluminum powder, 1-3 parts of flux, 3-7 parts of ball clay, 8-12 parts of bentonite, and 13-17 parts of silica sol adhesive.

[0005] The low-temperature sintered thin ceramic tile of the present application can be sintered at a temperature of 1000-1100°C through the mutual cooperation between the raw materials, reducing energy consumption and reducing the amount of waste gas emissions during the sintering process, which is conducive to industrial production. In addition, the thin ceramic tile has a breaking strength of >960N, a rupture modulus of >63MPa, and a water absorption rate of <0.2%. It has the advantages of high breaking strength, high rupture modulus, and low water absorption rate, showing good comprehensive performance and meeting market demand.

[0006] Adding flake graphite, aluminum borate whiskers, and aluminum oxide fibers to the raw materials of thin ceramic tiles can not only facilitate heat transfer, accelerate heat conduction, and reduce overburning, but also increase the fluidity between the raw materials, reduce apparent porosity, and improve density. Aluminum sulfate whiskers and aluminum oxide fibers can also increase the density of thin ceramic tiles, and with flake graphite, through the synergistic effect between the three, a dense cross network is formed, the grain structure is stabilized, the integrity is improved, the destructive strength and rupture modulus of thin ceramic tiles are enhanced, the water absorption rate is reduced, the quality of thin ceramic tiles is improved, the application range is expanded, the stability of use is increased, and the service life is extended.

[0007] Optionally, the average particle size of the flake graphite is 1-100 μm.

[0008] By adopting the above technical solution, the particle size of flake graphite is limited, which not only ensures the stability of the source of flake graphite, but also makes the flake graphite evenly dispersed in the thin ceramic tile, increases the density of the thin ceramic tile, and improves the mechanical properties of the thin ceramic tile. In multiple implementation schemes, the average particle size of flake graphite is 75μm, and the average particle size can also be set to 1μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm as needed, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0009] Optionally, the aluminum borate whiskers have an average length of 5-30 μm and an average diameter of 0.5-1 μm.

[0010] By adopting the above technical solution, the length and diameter of the aluminum borate whiskers are limited, which not only ensures the stability of the source of the aluminum borate whiskers, but also makes the aluminum borate whiskers evenly dispersed in the thin ceramic tiles, so that the thin ceramic tiles form a stable cross network, enhance the structural stability of the thin ceramic tiles, and ensure the quality of the thin ceramic tiles. In multiple implementation schemes, the average length of the aluminum borate whiskers is 10 μm and the average diameter is 0.8 μm. The average length can also be set to 5 μm, 15 μm, 20 μm, 25 μm, 30 μm as needed, and the average diameter can also be set to 0.5 μm, 0.6 μm, 0.7 μm, 0.9 μm, 1 μm as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0011] Optionally, the aluminum oxide fibers have an average length of 10-100 μm and an average diameter of 1-5 μm.

[0012] By adopting the above technical solution, the length and diameter of the aluminum oxide fiber are limited, which not only ensures the stability of the source of the aluminum oxide fiber, but also makes the aluminum oxide fiber evenly dispersed in the thin ceramic tile, which can also enhance the structural stability of the thin ceramic tile and extend the service life of the thin ceramic tile. In multiple implementation schemes, the average length of the aluminum oxide fiber is 50 μm and the average diameter is 3 μm. The average length can also be set to 10 μm, 20 μm, 30 μm, 40 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm as needed, and the average diameter can also be set to 1 μm, 2 μm, 4 μm, 5 μm as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] Optionally, the flux is one or more of boric acid, borax, phosphoric acid, and silicic acid.

[0014] By adopting the above technical solution, the flux is optimized and the selection of the flux is convenient. Moreover, the flux can reduce the sintering temperature and save energy. At the same time, the flux melts at high temperature, so that the raw materials are better melted and bonded together, and the density and mechanical strength of the thin ceramic tile are increased.

[0015] Optionally, the micron metal oxide is one or more of aluminum oxide, silicon dioxide, and titanium dioxide.

[0016] By adopting the above technical solution, the micron metal oxide is optimized, which is convenient for the selection of micron metal oxide. In addition, the micron metal oxide can increase the fluidity between raw materials, increase the density and uniformity of thin ceramic tiles, improve the flexural strength and high temperature resistance, and make the thin ceramic tiles show better comprehensive performance.

[0017] Optionally, the micron metal oxide is aluminum oxide and silicon dioxide, and the weight ratio of aluminum oxide to silicon dioxide is (1-3): (1-3). In multiple embodiments, the weight ratio of aluminum oxide to silicon dioxide is 1:1, and the weight ratio can also be set to 1:2, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0018] Optionally, the thickness of the thin ceramic tile is 2-7 mm.

[0019] By adopting the above technical solution, the thickness of thin ceramic tiles is limited, which is convenient for the production of thin ceramic tiles. Moreover, the thickness of thin ceramic tiles is controlled within the range of 2-7mm, which can ensure that the thin ceramic tiles have good mechanical properties and durability and meet the lightweight requirements. In multiple implementation schemes, the thickness of the thin ceramic tiles is 5.5mm, and the thickness can also be set to 2mm, 3mm, 4mm, 5mm, 6mm, 7mm as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] In a second aspect, the present application provides a method for producing low-temperature sintered thin ceramic tiles, which adopts the following technical solution: A method for producing low-temperature sintered thin ceramic tiles mainly comprises the following steps: S1. Mix pyrophyllite, potassium feldspar, sodium feldspar, mullite, quartz sand, micron metal oxides, flake graphite, aluminum borate whiskers, aluminum oxide fiber, metal aluminum powder, flux, ball clay, and bentonite, and add a silica sol binder to obtain a mixed material; S2, placing the mixed material in a mold, pressing and molding, and drying to constant weight to obtain a green body; S3, sintering the green body, cooling it to room temperature, and obtaining a thin ceramic tile.

[0021] By adopting the above technical solution, the preparation of thin ceramic tiles is facilitated.

[0022] Optionally, in step S2, the pressing pressure is 20-30 MPa and the time is 20-30 s.

[0023] By adopting the above technical solution, the pressure and time of press molding are limited, the situation of excessive porosity or insufficient compaction caused by insufficient pressure or too short time is reduced, and the green body is ensured to have a higher density and uniformity during the pressing process, so that the thin ceramic tile exhibits better comprehensive performance. In multiple implementation schemes, the pressure of press molding is 25MPa and the time is 25s. The pressure can also be set to 20MPa, 22MPa, 28MPa, 30MPa as needed, and the time can also be set to 20s, 22s, 28s, 30s as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Optionally, in step S3, the sintering temperature is 1000-1100° C. and the sintering time is 30-50 min.

[0025] By adopting the above technical scheme, the sintering temperature and time are limited, so that the green body is fully sintered to ensure the stability of the thin ceramic tile structure. Moreover, compared with the traditional sintering temperature of more than 1200°C, the sintering temperature of the present application is 1000-1100°C, which reduces energy consumption and reduces the amount of waste emissions during the sintering process, which is conducive to industrial production and application. In multiple implementation schemes, the sintering temperature is 1070°C and the time is 40 minutes. The temperature can also be set to 1000°C, 1020°C, 1050°C, and 1100°C as needed. The time can also be set to 30 minutes, 35 minutes, 45 minutes, and 50 minutes as needed, but it is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0026] In summary, this application has at least the following beneficial effects: The low-temperature sintered thin ceramic tile of the present application can realize sintering at a temperature of 1000-1100°C through the mutual cooperation between the raw materials, reduce energy consumption, and reduce the amount of waste gas emissions during the sintering process. In addition, flake graphite, aluminum borate whiskers, and aluminum oxide fibers are added to the raw materials at the same time, and the synergistic effect between the three is utilized to accelerate heat transfer, increase fluidity, reduce apparent porosity, improve density, form a dense cross network, stabilize the grain structure, improve integrity, enhance the destructive strength and rupture modulus of thin ceramic tiles, and reduce the water absorption rate of thin ceramic tiles. The destructive strength is greater than 960N, the rupture modulus is greater than 63MPa, and the water absorption rate is less than 0.2%, showing the advantages of high destructive strength, high rupture modulus, and low water absorption, improving the quality of thin ceramic tiles, expanding the scope of application, increasing the stability of use, and extending the service life to meet market demand. DETAILED DESCRIPTION

[0027] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified. Example

[0028] Table 1 Raw material dosage of thin ceramic tiles (unit: ×10g) Example 1 A low-temperature sintered thin ceramic tile, the thickness of the thin ceramic tile is 5.5 mm, and the raw material ratio is shown in Table 1.

[0029] Among them, the mesh number of pyrophyllite is 100 mesh, the silica content in pyrophyllite is 67wt%, and the aluminum oxide content is 28wt%; the mesh number of potassium feldspar is 150 mesh, the silica content in potassium feldspar is 63wt%, the aluminum oxide content is 23wt%, and the potassium oxide content is 9wt%; the mesh number of albite is 150 mesh, the silica content in albite is 68wt%, the aluminum oxide content is 22wt%, and the sodium oxide content is 10wt%; the mesh number of mullite is 150 mesh, the silica content in mullite is 27wt%, and the aluminum oxide content is 71wt%; the mesh number of quartz sand is 200 mesh, the silica content in quartz sand is 98wt%, and the aluminum oxide content is 1wt%.

[0030] The micron metal oxides are aluminum oxide and silicon dioxide, and the weight ratio of aluminum oxide to silicon dioxide is 1:1, the average particle size of aluminum oxide is 3μm, and the average particle size of silicon dioxide is 5μm; the average particle size of flake graphite is 75μm, and it is selected from Hebei Qingjiang New Material Technology Co., Ltd.; the average length of aluminum borate whiskers is 10μm and the average diameter is 0.8μm; the average length of aluminum oxide fibers is 50μm and the average diameter is 3μm, and the average particle size of metal aluminum powder is 80μm; the flux is boric acid, and the average particle size of boric acid is 75μm; the average particle size of ball clay is 5μm, and the silica content in the ball clay is 48wt% and the aluminum content is 34wt%; the average particle size of bentonite is 15μm, and the silica content in the bentonite is 65wt% and the aluminum content is 18wt%; the silica sol adhesive is silica sol JN-30.

[0031] A method for producing low-temperature sintered thin ceramic tiles mainly comprises the following steps: S1. Add potassium feldspar, sodium feldspar, mullite, quartz sand, micron metal oxide, flake graphite, aluminum borate whisker, aluminum oxide fiber, metal aluminum powder, flux, ball clay, and bentonite to pyrophyllite, stir for 2 minutes, add silica sol binder, stir for 10 minutes, and obtain a mixture.

[0032] S2. Place the mixed material in a mold, press and mold it for 25 seconds at a pressure of 25 MPa, and dry it to constant weight to obtain a green body.

[0033] S3. Sinter the green body at 1070°C for 40 minutes, then cool to 25°C to obtain a thin ceramic tile.

[0034] Example 2 A low-temperature sintered thin ceramic tile, which is different from Example 1 in that the raw material ratio of the thin ceramic tile is different. The raw material ratio of the thin ceramic tile is shown in Table 1.

[0035] Example 3 A low-temperature sintered thin ceramic tile, which is different from Example 1 in that the raw material ratio of the thin ceramic tile is different. The raw material ratio of the thin ceramic tile is shown in Table 1.

[0036] Example 4 A low-temperature sintered thin ceramic tile, which is different from Example 1 in that the raw material ratio of the thin ceramic tile is different. The raw material ratio of the thin ceramic tile is shown in Table 1.

[0037] Example 5 A low-temperature sintered thin ceramic tile, which is different from Example 1 in that the raw material ratio of the thin ceramic tile is different. The raw material ratio of the thin ceramic tile is shown in Table 1.

[0038] Comparative Example Comparative Example 1 A low-temperature sintered thin ceramic tile, which differs from Example 1 in that no flake graphite, aluminum borate whisker, or aluminum oxide fiber is added to the raw materials of the thin ceramic tile.

[0039] Comparative Example 2 A low-temperature sintered thin ceramic tile, which differs from Example 1 in that an equal amount of flake graphite is used to replace aluminum borate whiskers and aluminum oxide fibers in the raw materials of the thin ceramic tile.

[0040] Comparative Example 3 A low-temperature sintered thin ceramic tile, which differs from Example 1 in that an equal amount of aluminum borate whiskers is used to replace flake graphite and aluminum oxide fiber in the raw materials of the thin ceramic tile.

[0041] Comparative Example 4 A low-temperature sintered thin ceramic tile, which differs from Example 1 in that an equal amount of aluminum oxide fibers are used to replace flake graphite and aluminum borate whiskers in the raw materials of the thin ceramic tile.

[0042] Comparative Example 5 A low-temperature sintered thin ceramic tile, which differs from Example 1 in that in the raw materials of the low-thin ceramic tile, equal amounts of flake graphite and aluminum borate whiskers are used to replace aluminum oxide fibers, and the weight ratio of flake graphite and aluminum borate whiskers is 1:1.

[0043] Comparative Example 6 A low-temperature sintered thin ceramic tile, which differs from Example 1 in that in the raw materials of the low-thin ceramic tile, equal amounts of flake graphite and alumina fiber are used to replace aluminum borate whiskers, and the weight ratio of flake graphite to alumina fiber is 5:7.

[0044] Comparative Example 7 A low-temperature sintered thin ceramic tile, which differs from Example 1 in that in the raw materials of the low-thin ceramic tile, equal amounts of aluminum borate whiskers and aluminum oxide fibers are used to replace flake graphite, and the weight ratio of aluminum borate whiskers to aluminum oxide fibers is 5:7.

[0045] Performance Testing The thin ceramic tiles obtained in Examples 1-5 and Comparative Examples 1-7 were respectively taken, and the following performance tests were performed on the thin ceramic tiles. The test results are shown in Table 2.

[0046] Among them, GB / T3810.4-2016 "Ceramic Tile Test Methods Part 4: Determination of Rupture Modulus and Destructive Strength" is used to test the destructive strength and rupture modulus of thin ceramic tiles.

[0047] GB / T3810.3-2016 “Test methods for ceramic tiles Part 3: Determination of water absorption, apparent porosity, apparent relative density and bulk density” was used to test the water absorption of thin ceramic tiles.

[0048] Table 2 Test results Test items Destruction strength / (N) Modulus of rupture / (MPa) Water absorption / (%) Example 1 987 66.8 0.08 Example 2 971 64.3 0.15 Example 3 976 65.1 0.12 Example 4 981 65.9 0.10 Example 5 966 63.1 0.18 Comparative Example 1 854 43.3 0.63 Comparative Example 2 873 46.4 0.56 Comparative Example 3 891 49.8 0.47 Comparative Example 4 882 48.1 0.53 Comparative Example 5 925 55.7 0.35 Comparative Example 6 914 53.6 0.38 Comparative Example 7 936 57.2 0.28 As can be seen from Table 2, the thin ceramic tiles of the present application have high destructive strength and rupture modulus, with a destructive strength of 966-987N and a rupture modulus of 63.1-66.8MPa, which makes the thin ceramic tiles show the advantages of high destructive strength and high rupture modulus. And it also has a low water absorption rate, with a water absorption rate of 0.08-0.18%, which makes the thin ceramic tiles show the advantage of low water absorption. The thin ceramic tiles of the present application, through the mutual coordination between the raw materials, not only have a low sintering temperature, but also have the advantages of high destructive strength, high rupture modulus and low water absorption, showing better comprehensive performance and meeting market demand.

[0049] Comparative Examples 1-4 are compared. In Comparative Example 1, no flake graphite, aluminum borate whisker, or aluminum oxide fiber is added to the raw materials of the thin ceramic tile; in Comparative Example 2, flake graphite is added to the raw materials of the thin ceramic tile; in Comparative Example 3, aluminum borate whisker is added to the raw materials of the thin ceramic tile; in Comparative Example 4, aluminum oxide fiber is added to the raw materials of the thin ceramic tile. It can be seen that adding flake graphite alone, or adding aluminum borate whisker alone, or adding aluminum oxide fiber alone to the raw materials can improve the destructive strength and rupture modulus of thin ceramic tiles.

[0050] Compare with Comparative Examples 5-7. In Comparative Example 5, flake graphite and aluminum borate whiskers are added to the raw materials of the thin ceramic tiles; in Comparative Example 6, aluminum borate whiskers and aluminum oxide fibers are added to the raw materials of the thin ceramic tiles; in Comparative Example 7, aluminum borate whiskers and aluminum oxide fibers are added to the raw materials of the thin ceramic tiles. It can be seen that adding flake graphite and aluminum borate whiskers, or aluminum borate whiskers and aluminum oxide fibers, or aluminum borate whiskers and aluminum oxide fibers to the raw materials are beneficial to improving the mechanical properties of thin ceramic tiles. Compare with Example 1 for comparison. In Example 1, flake graphite, aluminum borate whiskers and aluminum oxide fibers are added to the raw materials of the thin ceramic tiles. From this, it can be seen that by adding flake graphite, aluminum borate whiskers and aluminum oxide fibers to the raw materials at the same time and utilizing the synergistic effect among the three, a cross-network structure can be formed in the thin ceramic tiles, increasing the stability, density and uniformity of the thin ceramic tiles structure, improving the destructive strength and rupture modulus of the thin ceramic tiles, while also reducing the water absorption of the thin ceramic tiles, so that the thin ceramic tiles exhibit better overall performance.

[0051] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A low-temperature sintered thin ceramic tile, characterized in that: Thin ceramic tiles are mainly made of the following raw materials in parts by weight: 15-25 parts of pyrophyllite, 10-20 parts of potassium feldspar, 10-20 parts of sodium feldspar, 10-20 parts of mullite, 20-30 parts of quartz sand, 6-10 parts of micron metal oxides, 4-6 parts of flake graphite, 4-6 parts of aluminum borate whiskers, 6-8 parts of aluminum oxide fibers, 2-4 parts of metallic aluminum powder, 1-3 parts of flux, 3-7 parts of ball clay, 8-12 parts of bentonite, and 13-17 parts of silica sol adhesive.

2. A low temperature sintered thin ceramic tile according to claim 1, characterized in that: The average particle size of the flake graphite is 1-100 μm.

3. The low-temperature sintered thin ceramic tile according to claim 1, characterized in that: The aluminum borate whiskers have an average length of 5-30 μm and an average diameter of 0.5-1 μm.

4. The low-temperature sintered thin ceramic tile according to claim 1, characterized in that: The aluminum oxide fibers have an average length of 10-100 μm and an average diameter of 1-5 μm.

5. The low-temperature sintered thin ceramic tile according to claim 1, characterized in that: The flux is one or more of boric acid, borax, phosphoric acid and silicic acid.

6. The low-temperature sintered thin ceramic tile according to claim 1, characterized in that: The micron metal oxide is one or more of aluminum oxide, silicon dioxide and titanium dioxide.

7. The low-temperature sintered thin ceramic tile according to claim 1, characterized in that: The thickness of the thin ceramic brick is 2-7 mm.

8. A method for producing a low-temperature sintered thin ceramic tile according to any one of claims 1 to 7, characterized in that: The main steps are as follows: S1. Mix pyrophyllite, potassium feldspar, sodium feldspar, mullite, quartz sand, micron metal oxides, flake graphite, aluminum borate whiskers, aluminum oxide fiber, metal aluminum powder, flux, ball clay, and bentonite, and add a silica sol binder to obtain a mixed material; S2, placing the mixed material in a mold, pressing and forming, and drying to constant weight to obtain a green body; S3, sintering the green body, cooling it to room temperature, and obtaining a thin ceramic tile.

9. The method for producing a low-temperature sintered thin ceramic tile according to claim 8, characterized in that: In step S2, the pressure of the pressing molding is 20-30 MPa and the time is 20-30 s.

10. The method for producing a low-temperature sintered thin ceramic tile according to claim 8, characterized in that: In step S3, the sintering temperature is 1000-1100° C. and the sintering time is 30-50 min.

Citation Information

Cited By

  • Fiber reinforced ceramic tile and production method thereof

    CN122212790A

  • Fiber reinforced ceramic tile and method of production thereof

    CN122212790B